"In nomine Domini". Zum 100. Geburtstag des Komponisten Giselher Klebe - Höink, Dominik (Musik & Kirche)

Friedrich Schneider, Christus der Meister. Oratorium in drei Teilen. Partitur

Digitalisierung und Künstliche Intelligenz - Steinhardt, Isabel (Hochschulforschung)
In diesem Beitrag wird ein Überblick gegeben, welche Forschung zu Digitalisierung und künstliche Intelligenz (KI) in den Bereichen Verwaltung, Forschung, Studium und Lehre sowie Governance von Hochschulen besteht. Der Fokus liegt hierbei auf aktuellen Forschungsergebnissen seit der Coronapandemie. Zentral sind Fragen nach Effektivität und Effizienz durch Digitalisierung und KI und danach, wie Verbesserungen angestoßen werden können.
Keywords: Digitalisierung; Künstliche Intelligenz; Forschung; Lehre; Governance; Verwaltung

Open Science - Steinhardt, Isabel; Röwert, Ronny (Hochschulforschung)
In diesem Beitrag wird zunächst die historische Entstehung von Open Science kurz skizziert und definiert, was unter diesem Begriff zu verstehen ist. Daran anschließend werden die Open-Science-Praktiken Open Data, Open Access, Open Source, Open Methodology und Open Peer Review dargestellt und diskutiert, welche Forschungserkenntnisse zu Open Science vorhanden sind. Im Schluss werden Forschungsdesiderate aufgegriffen und die Implikationen von Open Science für die Wissenschaft erläutert.
Keywords: Open Data; Open Access; Open Source; Open Methodology; Open Peer Review

Quantum teleportation with dissimilar quantum dots over a hybrid quantum network - Laneve, Alessandro; Ronco, Giuseppe; Beccaceci, Mattia; Barigelli, Paolo; Salusti, Francesco; Claro-Rodriguez, Nicolas; De Pascalis, Giorgio; Suprano, Alessia; Chiaudano, Leone; Schöll, Eva; Hanschke, Lukas; Krieger, Tobias M.; et al. (Nature Communications)

Teaching Hypotheses with Émilie du Châtelet - Hagengruber, Ruth Edith; Velema, Floris (Journal of Didactics of Philosophy)

KI als Herausforderungen für die qualitative Methodenlehre – ein Diskussionsaufruf! - Schmidt, Rebecca (Sozialwissenschaftliche Methodenberatung)

Rezension von Simone Amorocho (2024): Mündliche Prüfungen in der Pflegeausbildung. Eine gesprächsanalytische Studie zu sprachlichen und interaktionalen Anforderungen - Prikoszovits, Matthias

Photorefraction and in-situ optical cleaning in various types of LiNbO3 waveguides - Kirsch, Michelle; Kießler, Christian; Lengeling, Sebastian; Stefszky, Michael; Eigner, Christof; Herrmann, Harald; Silberhorn, Christine (Optics & Laser Technology)
Lithium niobate (LiNbO3) is a widely used material with several desirable physical properties, such as high second-order nonlinear optical and strong electro-optical effects. Thus LiNbO3 is used for various applications such as electro-optic modulation or nonlinear frequency conversion and mixing. But LiNbO3 also exhibits a strong photorefractive effect, which limits the intensity of the optical fields involved. Various approaches to reduce the photorefractive effect have been investigated, such as increasing the temperature, doping the crystal or using different waveguide designs in LiNbO3. Here, we present an analysis of the approach to increase the photorefractive damage threshold by using different waveguide designs. Contrary to previous claims and investigations, our SHG measurements revealed no significant difference in resistance to photorefractive damage when comparing conventional Ti-doped channel waveguides and Ti-doped diced ridge waveguides in LiNbO3. Furthermore, we have investigated the effect of photorefractive cleaning and curing using a light field at 532 nm. Here, we observe a reduction in the photorefractive effect at room temperature during and after SHG measurements, which is an easy alternative to conventional approaches.

La corte como mare errorum en La Cisma de Ingalaterra - Schlieper, Hendrik (Cálculo y error. Recontando a Calderón. XX Coloquio Anglogermano sobre Calderón)

Facilitating the Automated Generation of Data-Driven Models for the Diagnostics and Prognostics of Technical Systems - Löwen, Alexander; Quirin, Dennis; Hesse, Marc; Aimiyekagbon, Osarenren Kennedy; Sextro, Walter (2025 IEEE 30th International Conference on Emerging Technologies and Factory Automation (ETFA))
The integration of data-driven models and specifically machine learning for conditon monitoring and predictive maintenance into companies, especially small and medium-sized enterprises, offers significant opportunities in reducing costs, operating more sustainably, and maintaining long-term competitiveness. However, many small and medium-sized enterprises lack the necessary resources and expertise to derive knowledge from data and integrate their own machine learning based solutions. To address this challenge, a framework is presented that enables the automated generation of data-driven models with a particular focus on condition monitoring and predictive maintenance, but applicable to other use cases as well. Using a dataset from the 2022 data challenge of the prognostics and health management society, it is demonstrated that the framework can generate high-performing models, achieving F1-scores up to 0.998, exemplarily for a classification task.

Professionelle Wahrnehmung der Anforderungssituation 'Gespräche zum flexiblen Rechnen moderieren': Ein Vergleich zwischen angehenden und erfahrenen Lehrkräften mittels Epistemic Network Analysis - Becker, Federica
Im Beitrag wird die professionelle Unterrichtswahrnehmung von (angehenden) Lehrkräften bezogen auf die Anforderungssituation 'Gemeinsam Gespräche moderieren' im Kontext des flexiblen Rechnens in Jahrgangsstufe 1 betrachtet. Die Studie untersucht mittels Videovignetten expertise-bezogene Unterschiede in der professionellen Wahrnehmung, indem je 10 angehende und erfahrene Mathematiklehrkräfte betrachtet werden. Die zunächst inhaltsanalytisch ausgewerteten Daten der beiden Gruppen werden mittels der epistemischen Netzwerkanalyse verglichen. Es werden erste Ergebnisse berichtet.

Genese und Stand der Weiterentwicklung der Profile im Lehramtsstudium an der Universität Paderborn - Decker, Claudia

Trust Me If You Can! Examining the Role of Ransomware Darknet Platforms in Building Trust Between Hackers and Victims - Hövel, Gilbert Georg; Brinkmeier, Tim; Trang, Simon Thanh-Nam (Proceedings of the International Conference on Information Systems 2025)

Complementarity-based complementarity: The choice of mutually unbiased observables shapes quantum uncertainty relations - Serino, Laura Maria; Chesi, Giovanni; Brecht, Benjamin; Maccone, Lorenzo; Macchiavello, Chiara; Silberhorn, Christine (Physical Review Research)
Quantum uncertainty relations impose fundamental limits on the joint knowledge that can be acquired from complementary observables: Perfect knowledge of a quantum state in one basis implies maximal indetermination in all other mutually unbiased bases (MUBs). Uncertainty relations derived from joint properties of the MUBs are generally assumed to be uniform, irrespective of the specific observables chosen within a set. In this work, we demonstrate instead that the uncertainty relations can depend on the choice of observables. Through both experimental observation and numerical methods, we show that selecting different sets of three MUBs in a five-dimensional quantum system results in distinct uncertainty bounds, i.e., in varying degrees of complementarity, in terms of both entropy and variance.

Physik in der Lehrerinnen- und Lehrerbildung - Empirisch fundierte Curricula in einer digitalen Welt - Riese, Josef; Reinhold, Peter (Handbuch Lehrerinnen- und Lehrerbildung)

Edge-coloring 4- and 5-regular projective planar graphs with no Petersen-minor - Kidner, Arnott Jeffery Joel; Steffen, Eckhard; Yu, Weiqiang (arXiv:2512.14285)

Time-resolved second-order autocorrelation function of parametric down-conversion - Horoshko, Dmitri B.; Srivastava, Shivang; Sośnicki, Filip; Mikołajczyk, Michał; Karpiński, Michał; Brecht, Benjamin; Kolobov, Mikhail I. (Physical Review A)
We study a possibility of measuring the time-resolved second-order autocorrelation function of one of two beams generated in type-II parametric down-conversion by means of temporal magnification of this beam, bringing its correlation time from the picosecond to the nanosecond scale, which can be resolved by modern photodetectors. We show that such a measurement enables one to infer directly the degree of global coherence of that beam, which is linked by a simple relation to the number of modes characterizing the entanglement between the two generated beams. We illustrate the proposed method by an example of photon pairs generated in a periodically poled potassium titanyl phosphate (KTP) crystal with a symmetric group velocity matching for various durations of the pump pulse, resulting in different numbers of modes. Our theoretical model also shows that the magnified double-heralded autocorrelation function of one beam exhibits a local maximum around zero delay time, corresponding to photon bunching at a short time scale.

Self-guided tomography of time-frequency qudits - Serino, Laura Maria; Rambach, Markus; Brecht, Benjamin; Romero, Jacquiline; Silberhorn, Christine (Quantum Science and Technology)
Abstract High-dimensional time-frequency encodings have the potential to significantly advance quantum information science; however, practical applications require precise knowledge of the encoded quantum states, which becomes increasingly challenging for larger Hilbert spaces. Self-guided tomography (SGT) has emerged as a practical and scalable technique for this purpose in the spatial domain. Here, we apply SGT to estimate time-frequency states using a multi-output quantum pulse gate. We achieve fidelities of more than 99% for 3- and 5-dimensional states without the need for calibration or post-processing. We demonstrate the robustness of SGT against statistical and environmental noise, highlighting its efficacy in the photon-starved regime typical of quantum information applications.

The Frequency‐Domain Lattice Boltzmann Method (FreqD‐LBM): A Versatile Tool to Predict the QCM Response Induced by Structured Samples - Johannsmann, Diethelm; Häusner, Paul; Langhoff, Arne; Leppin, Christian; Reviakine, Ilya; Vanoppen, Viktor (Advanced Theory and Simulations)
Abstract The quartz crystal microbalance with dissipation monitoring (QCM‐D) is routinely used to investigate structured samples. Here, a simulation technique is described, that predicts the shifts of frequency and half bandwidth, Δ f n and ΔΓ n , of a quartz resonator operating on different overtone orders, n , induced by structured samples in contact with the resonator surface in liquid. The technique, abbreviated as FreqD‐LBM, solves the Stokes equation in the frequency domain. The solution provides the complex amplitude of the area‐averaged tangential stress at the resonator surface, from which Δ f n and ΔΓ n are derived. Because the dynamical variables are complex amplitudes, the viscosity can be complex, as well. The technique naturally covers viscoelasticity. Limitations are linked to the grid resolution and to problems at large viscosity. Validation steps include viscoelastic films, rough surfaces, an oscillating cylinder in a viscous medium, and a free‐floating sphere above the resonator. Application examples are soft adsorbed particles, stiff adsorbed particles, and a large, immobile spherical cap above the resonator, which allows to study the high‐frequency properties of the material in the gap. FreqDLBM runs on an office PC and does not require expert knowledge of numerical techniques. It is accessible to an experimentalist.